2022
DOI: 10.1253/circj.cj-21-0315
|View full text |Cite
|
Sign up to set email alerts
|

New Ultrasound-Controlled Paclitaxel Releasing Balloon vs. Asymmetric Drug-Eluting Stent in Primary ST-Segment Elevation Myocardial Infarction ― A Prospective Randomized Trial ―

Abstract: the agent is rapidly released locally into the vessel wall. 9 This technology allows a broader area of surface contact and more homogenous drug-tissue transfer compared to stent-based local drug delivery. 10 CAD patients treated with DCB angioplasty may benefit from the absence of a permanent stent and shortened dual antiplatelet therapy. 11-13 DCB application was first recommended by the European Society of Cardiology (ESC) and European Association for Cardio-Thoracic Surgery (EACTS) guidelines for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Our meta-analysis included 13 studies of 2644 patients comparing DCB with DES [ 10 , 16 , 18 – 28 ]. All included studies assessed our primary outcome, MACE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis included 13 studies of 2644 patients comparing DCB with DES [ 10 , 16 , 18 – 28 ]. All included studies assessed our primary outcome, MACE.…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical trials have also demonstrated its value in bifurcation lesions, diffuse disease, chronic total occlusions, high blood risk conditions, calcified complex lesions, and even in de novo large vessel disease [ 13 15 ]. Although some recent clinical trials have evaluated the feasibility of DCB for the treatment of AMI patients [ 10 , 16 ], these individual studies do not provide very strong evidence of the exact efficacy of DCB for AMI. The effects of DCB in the treatment of AMI are still less well known.…”
Section: Introductionmentioning
confidence: 99%
“…Following 165 studies remained to be read the full text for further exclusion. Finally, 10 articles [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] were included in our meta-analysis, with an overall population of 1468 patients. Among them, 717 (48.8 %) were randomized to a DCB strategy, while 751 (51.2 %) patients to a Stent strategy.7 trials [ 10 , 11 , 14 , [16] , [17] , [18] , [19] ] involving 1010 patients in the control group with DES, 2 trials [ 12 , 13 ] involving 248 patients in the control group with BMS, and one trials [ 15 ] involving 210 patients in the control group with DES or BMS.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 10 articles [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] were included in our meta-analysis, with an overall population of 1468 patients. Among them, 717 (48.8 %) were randomized to a DCB strategy, while 751 (51.2 %) patients to a Stent strategy.7 trials [ 10 , 11 , 14 , [16] , [17] , [18] , [19] ] involving 1010 patients in the control group with DES, 2 trials [ 12 , 13 ] involving 248 patients in the control group with BMS, and one trials [ 15 ] involving 210 patients in the control group with DES or BMS. Four trials [ 11 , 14 , 16 , 18 ] included only patients with STEMI, while five trials [ 10 , 12 , 13 , 15 , 19 ] excluded patients with STEMI, and one trial's [ 17 ] population had unspecified de novo coronary lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the feasibility data of DCB PCI in large vessels come from sub-analysis of larger observational retrospective or prospective studies with few dedicated studies. Data obtained from observational studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] are summarized in Table 1 , whereas randomized studies comparing DCB and stent are presented in Table 2 and Table 3 [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: A New Frontier: Large Vessel Coronary Artery Diseasementioning
confidence: 99%